Species at risk: a guide for Canadian entomologists. Issue 4 (21st June 2019) - Timms, Laura L.; Rix, Rachel R.
Abstract: The collection and preservation of insect specimens supply valuable information to entomologists. Collections are foundational to natural history, and paramount to the study of life history, systematics, and evolution. Rising concern over anthropogenic loss of biodiversity, including insect losses, has led to policies, strategies, and procedures being put in place in Canada to ensure the protection of wildlife species at risk. This document outlines necessary information to help researchers ensure that they are in compliance with Canadian legislation when carrying out research involving the collection of insects. We include an overview of the federal Species at Risk Act, and provincial and territorial legislation protecting at-risk wildlife, and how wildlife species in Canada ranked and are assessed as being at risk. We also discuss prohibitions outlined in the federal Species at Risk Act and penalties for violating these prohibitions; providing examples from case histories on convictions under the act.